AUGMENTED REALITY MEDIA FOR LEARNING ELECTRICAL CIRCUITS: ENHANCING SCIENCE PROCESS SKILLS AND STUDENTS’ ACHIEVEMENT - Niati, Nendi; Murti, Rahayu Condro; Hastuti, Woro Sri (JURNAL EDUSCIENCE, 2025)
Purpose—The study aims to develop Android-based augmented reality (AR) instructional media for teaching electrical circuits, enhancing students' science process skills and learning outcomes. In addition, this technology can help students develop the science process skills needed in science learning.Methodology—The research was conducted with 29 fifth–grade students at SDN 09 Rangkang, Bengkayang, Using the ADDIE development model (analysis, design, development, implementation, and evaluation). The instruments used at this stage included expert validation sheets, science process skills questionnaires, learning outcome tests, and observation sheets. Data analysis is conducted descriptively and quantitatively to assess the media's validity, practicality, and effectiveness.Findings – The media’s validity was rated highly, with an average expert validation score of 87, while its practicality was deemed suitable, with an average score of 80. The media was also effective as 86% of students achieved high-level science process skills, and 89% met the minimum passing criteria in the learning outcome test, with an average score of 82.Significance – The results indicate that the developed instructional media is valid, practical, and effective in improving the quality of teaching and learning.Keywords: Augmented Reality, Electrical Circuits, Students’ Achievement, Science Process Skills